TRANSFORMASI BADAN KREDIT DESA MENJADI LEMBAGA KEUANGAN MIKRO PERSPEKTIF HUKUM EKONOMI SYARIAH - A. Zaky Fuad; Asmawi Asmawi; Kutbuddin Aibak (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2022)
This research is motivated by the rise of the Financial Services Authority Regulation (POJK) 10/POJK.03/2016 concerning the Fulfillment of Provisions for Rural Banks and the Transformation of Village Credit Boards Given Status as Rural Banks, which this regulation requires BKD to make an action plan (action plan) and carry out the process of transformation into a financial institution that is legal and recognized by law. The focus and questions in this research are: (1) the transformation of BKD into an MFI before POJK Number 10 of 2016?; (2) transformation of BKD into MFI after POJK Number 10 of 2016?; and (3) transformation of BKD into MFI in the perspective of sharia economic law? This research employs empirical legal research with a sociological juridical approach, a conceptual approach, and a statutory approach. Data collection was carried out by participant observation, in-depth interviews with BUMDES in Genteng District and several related parties and documentation methods, then analysed using deduction, induction and comparative analysis. The results showed that the Bumdes Lembu Suro Genteng Kulon did not join the Bumdes Bersama, the Bumdes Lumbung Makmur Genteng Wetan joined the Bumdes Bersama and the Bumdes Rukun Makmur Kembiritan did not join the Bumdes Bersama. These three Bumdes have implemented the ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œThree New PillarsÃƒÂ¢Ã¢â€šÂ¬Ã‚Â initiated by William Richard Scott with three indicators, namely: regulatory, normative and cultural-cognitive. Each indicator has the following aspects of view: (1) the basis of compliance, (2) the basis of the rules, (3) the implementation mechanism, (4) the logic of sanctions, (5) the indicators for the consideration of sanctions, (6) the impact of the determination of sanctions, and (7) basis for determining legitimacy. Bumdes Lembu Suro Genteng Kulon in the "mechanism" aspect does not implement the scot concept (regulative, normative and cultural-cognitve), but implements a mechanism to build a communication mechanism between BKD or Bumdes management and the Regional Government, and if deemed necessary to facilitate the communication impasse as part from a normative aspect. Bumdes Lumbung Makmur Genteng Wetan in the "mechanism" aspect does not implement the scot concept (Regulative, Normative and Cultural-Cognitive), but implements a transformation mechanism or establishes an institution by means of "communication" as part of the normative aspect. Bumdes Rukun Makmur Kembiritan in the aspect of "mechanism" does not implement the Scott concept (Regulative, Normative and Cultural-Cognitive), but implements a transformation mechanism or establishes an institution by carrying out "facilitation and harmonization" as part of the normative aspect. These three Bumdes have the same perception of the necessity for BKD to transform after the issuance of POJK Number 10/POJK.03/ 2016. However, due to the lack of BKD data and the scarcity of BKD management, what is taken is not to transform, but directly to form or establish Bumdes with all its dynamics. In the perspective of Sharia Economic Law, that transformation or establishing institutions is part of the sunnatullah to change the situation towards better conditions and that implementing government policies as long as they are oriented to the benefit of the people is obligatory, even if the decisions or policies made by the government are not based on Islam. Whereas based on Scott's concept perspective, the implementation of government decisions or policies applies in totality, both in terms of legal basis, mechanism and institutional legitimacy basis. Then, that through the concept of qiyas or analogy, the transformation of BKD is included in the hiwalah contract (debt transfer). By analogy, BKD is analogous to muhal or dain (people who give debts or loans), Borrowers or Customers (individuals or groups) are analogous to muhil or madin (debtors), Bumdes or PT. LKM Bumdes Bersama is analogous to muhtal or muhtal alaih (the party who receives the transfer of debt/loans), Nominal Loans are analogous to muhal bih (debt/loan nominal). In the end there were several BKDs that did not carry out the transformation and there were BKDs that did not cooperate at the district level through PT. LKM Bumdes with Banyuwangi Regency.